2016
DOI: 10.4236/psych.2016.72019
|View full text |Cite
|
Sign up to set email alerts
|

How Are Parental Reactions to Children’s Emotions Related to Their Theory of Mind Abilities?

Abstract: In this study, parents' reactions to their children's emotions were investigated as correlates of children's abilities in Theory of Mind (ToM). 175 parents completed questionnaires about their reactions to their children's emotions. Children's ToM abilities were assessed by direct measures and a questionnaire completed by mothers. Inter-parental comparisons and intra-parental interactions were explored. The maternal model was significant for children's ToM-emotions and ToM-thinking. The paternal model was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
9
1
1
Order By: Relevance
“…Categorization of supportive and non-supportive reactions (Mazzone & Nader-Grosbois, 2016) Submit or recommend next manuscript to SCIRP and we will provide best service for you:…”
Section: Appendixmentioning
confidence: 99%
“…Categorization of supportive and non-supportive reactions (Mazzone & Nader-Grosbois, 2016) Submit or recommend next manuscript to SCIRP and we will provide best service for you:…”
Section: Appendixmentioning
confidence: 99%
“…Many studies revealed that supportive parental reactions to child's emotions are related to better child's abilities in Theory of Mind (ToM) (e.g., [1] [2]), or in emotional regulation (ER) (e.g., [3] [18] [22]) and in social adjustment (e.g., [7] [11]). While parental non-supportive reactions may impede the child's socio-emotional development.…”
Section: Ersbs and Socio-emotional Developmentmentioning
confidence: 99%
“…Concerning parents' characteristics, numerous studies revealed that parents' reactions to their child's emotions (e.g., [1] [13] [14]) and parents' emotionrelated conversations (e.g., [10] [15] [16]) vary depending on the parent's gender. Except the parent's gender, researchers have largely overlooked other parents' characteristics as potential predictors of their ERSBs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations